Which are the best identifiers for record linkage?. - Quantin, Catherine (Medical informatics and the intrenet in medicine :an international journal of information processing in health care.)
As a linkage using less informative identifiers could lead to linkage errors, it is essential to quantify the information associated to each identifier. The aim of this study was to estimate the discriminating power of different identifiers susceptible to be used in a record linkage process. This work showed the interest of three identifiers when linking data concerning a same patient using an automatic procedure based on the method proposed by Jaro; the date of birth, the first and the last names seemed to be the more appropriate identifiers. Including a poorly discriminating identifier like gender did not improve the results. Moreover, adding a second christian name, often missing, increased linkage errors. On the contrary, it seemed that using a phonetic treatment adapted to the French language could improve the results of linkage in comparison to the Soundex. However, whatever, the method used it seems necessary to improve the quality of identifier collection as it could greatly influence linkage results.